Circle Structure: Utilizing the Wisdom in the Room - Sortino, Lori (Allies for Education, 2017)
Lori Sortino suggests that by beginning in circle we can approach issues within our classroom, school site or district in a way that all voices are heard, needs can be met, and available resources can find their application with an emphasis on personal responsibility and compassion.